A Governance Framework for Implementation of Scientific and Engineering Innovation in Buried Infrastructure Systems - Shrimpton, Elisabeth A.; Hunt, Dexter V. L.; Rogers, Christopher D. F. (Frontiers in Sustainable Cities, 2022)
This article draws on experience within a pervasive sensing research project, the Pipebots project. The aim of the project is to design miniature robots to gather physical condition and environmental data on buried pipe networks, using potable water distribution and wastewater pipe systems as the initial target applications. One of the challenges of the project is to anticipate and address the potential governance issues triggered by the project. Due to the lack of a suitable tool with sufficient breadth to guide thinking, the existing literature has been drawn upon to form the basis of a governance framework for use in infrastructure projects. Whilst the original intention was to be alert to and interrogate the forms of governance that may impact on new infrastructure interventions, what is emerging is a tool that would support the strategy for implementation, improve the design (a no-regrets design policy) and help build the business case for the transformational change the project envisages